Melestarikan Tradisi Adat Istiadat Demi Terwujudnya Kerukunan Beragama di Indonesia di Tengah Arus Globalisasi - Purbarini, Sofy Diah Ayu; Wardah, Zahrotul; Nugraha, Mochammad Nur Ilham; Diniyah, Maftukhatut; Tafsir, Tafsir; Ismail, Ismail; Hidayatullah, Ahmad Fauzan (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
There are several cases of religious harmony on the day of Chinese New Year celebrations due to the globalization factor that occurs in religious communities. Chinese New Year celebrations from time to time of course there are differences. During the old order, Chinese New Year could not be separated from the political dimension. During the New Order era, the ethnic Chinese experienced government restraints and set the Presidential Instruction. The Presidential Instruction states that all Chinese religious ceremonies, beliefs, and customs may be performed only in a family environment and in an enclosed room.. However, at this time Chinese New Year is celebrated with open shows, such as lion dance performances and others. Chinese Muslims still carry out Chinese New Year celebrations even though they have embraced Islam. Thus they do not lose their ethnic identity, even though they have embraced Islam. This Chinese New Year celebration is also carried out by the Japanese people, precisely in Yokohama. Therefore, this tradition is followed by Chinese Muslims, Chinese Protestants, Chinese Catholics and Chinese Confucians.